Elaboration over a Discourse Facilitates Retrieval in Sentence Processing - Troyer, Melissa; Hofmeister, Philip; Kutas, Marta (Frontiers in Psychology, 2016)
Language comprehension requires access to stored knowledge and the ability to combine knowledge in new, meaningful ways. Previous work has shown that processing linguistically more complex expressions (‘Texas cattle rancher’ vs. ‘rancher’) leads to slow-downs in reading during initial processing, possibly reflecting effort in combining information. Conversely, when this information must subsequently be retrieved (as in filler-gap constructions), processing is facilitated for more complex expressions, possibly because more semantic cues are available during retrieval. To follow up on this hypothesis, we tested whether information distributed across a short discourse can similarly provide effective cues for retrieval. Participants read texts introducing two referents (e.g., two senators), one of whom was described in greater detail than the other (e.g., ‘The Democrat had voted for one of the senators, and the Republican had voted for the other, a man from Ohio who was running for president’). The final sentence (e.g., ‘The senator who the {Republican / Democrat} had voted for…’) contained a relative clause picking out either the Many-Cue referent (with ‘Republican’) or the One-Cue referent (with ‘Democrat’). We predicted facilitated retrieval (faster reading times) for the Many-Cue condition at the verb region (‘had voted for’), where readers could understand that ‘The senator’ is the object of the verb. As predicted, this pattern was observed at the retrieval region and continued throughout the rest of the sentence. Participants also completed the Author/Magazine Recognition Tests (ART/MRT; Stanovich & West, 1989), providing a proxy for world knowledge. Since higher ART/MRT scores may index (a) greater experience accessing relevant knowledge and/or (b) richer/more highly-structured representations in semantic memory, we predicted it would be positively associated with effects of elaboration on retrieval. We did not observe the predicted interaction between ART/MRT scores and Cue condition at the retrieval region, though ART/MRT interacted with Cue condition in other locations in the sentence. In sum, we found that providing more elaborative information over the course of a text can facilitate retrieval for referents, consistent with a framework in which referential elaboration over a discourse and not just local linguistic information directly impacts information retrieval during sentence processing.